FENOMENA BAHASA SLANG, BAHASA JARGON, DAN BAHASA PROKEM DALAM KOMUNIKASI SANTRI PONDOK PESANTREN DARUSSALAM PUTRI UTARA BLOKAGUNG BANYUWANGI - Ali Manshur; Siti Nur jannah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The phenomenon of the emergence of various languages ??used by groups which makes language users more creative and innovative. Especially students who have different cultural backgrounds. Often students communicate by changing the language that the students can understand only. The languages ??used are called slang, prokem, and pesantren jargon. The aims of this study were to: 1) describe the various forms of slang, jargon, and prokem in the communication of the students of the Darusaalm Putri Utara Islamic Boarding School. 2) Describe the meaning in the use of various pesantren languages ??in the communication of the students of the Darussalam Putri Utara Islamic Boarding School, Blokagung Banyuwangi. This study uses a qualitative descriptive method that can help identify various factors and information in the Darussalam Putri Utara Islamic Boarding School. The conclusions of this study: 1) Variety of langue; a) Islamic boarding school slang is a variety of languages ??that are special and secret, meaning that the language is only used in Islamic Boarding Schools with a total of 28 words. 2b) Pesantren jargon language is a variety of languages ??used in Islamic boarding schools, but they are not secret, totaling 27 words. c) Prokem language is a variety of slang used in daily communication to increase the intimacy between students, totaling 44 words. 2) The meaning of the variety of languages ??contained in each word of slang, jargon, and program boarding schools is the meaning given by the user as another form of the meaning of the basic word of the language variety.